Silicon nitride nanowire and preparation method thereof

By combining pioneer pyrolysis and carbon thermal reduction, silicon nitride nanowires were prepared using acrylate modified polysilazane, which solved the problems of complex preparation process and low product purity in the prior art, and achieved high purity and uniform morphology nanowire preparation, which was suitable for large-scale industrial production.

CN119774558AActive Publication Date: 2025-04-08SHANDONG UNIV OF TECH

Patent Information

Application Number
CN202510286035.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-08
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

The existing preparation methods for silicon nitride nanowires have problems such as complex preparation process, difficult to accurately control the reaction, low purity of the product and uneven size distribution. In particular, nanowires often contain metal impurities, which reduce the purity of the product.

Method used

Silicon nitride nanowires are prepared by combining pioneer pyrolysis and carbon thermal reduction without using catalysts and toxic and harmful nitrogen sources. The process is simple and environmentally friendly, and is suitable for large-scale industrial production.

Benefits of technology

It achieves high purity (more than 95%) and uniform morphology, controllable diameter (100~500nm), no catalyst required, environmentally friendly process, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774558A_ABST
    Figure CN119774558A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano material preparation, and particularly relates to a silicon nitride nanowire and a preparation method thereof. Comprising the following steps: (1) mixing vinyl polysilazane and acrylic acid 2-isocyano ethyl ester, and carrying out stirring reaction under a vacuum condition to obtain A-PSZ; (2) the A-PSZ is put into a vacuum drying oven to be subjected to thermocuring treatment, and cured A-PSZ is obtained; (3) putting the cured A-PSZ into a tubular furnace, and introducing N2 to carry out pyrolytic reaction; and (4) taking out the sample after the pyrolytic reaction, collecting a product generated on the surface of the sample, and sequentially carrying out acid washing and alkali washing treatment to finally obtain the silicon nitride nanowire. According to the method, acrylate modified polysilazane is taken as a raw material, precursor pyrolysis and carbon thermal reduction are combined, the prepared silicon nitride nanowire is high in purity and uniform in morphology, meanwhile, a catalyst and a toxic and harmful nitrogen source do not need to be used in the preparation process, and the method is environmentally friendly and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation, and specifically relates to silicon nitride nanowires and a preparation method thereof. Background Art

[0002] Silicon nitride nanowires, as a one-dimensional nanostructure of silicon nitride materials, have shown great application potential in many fields due to their unique advantages. They not only have excellent mechanical properties such as high flexibility and high tensile strength, but also have high thermal stability, excellent thermal shock resistance, outstanding chemical stability and excellent photoelectric properties. These characteristics enable silicon nitride nanowires to significantly improve the strength and toughness of silicon nitride ceramic materials when used as a ceramic matrix raw material; and when used as a composite material reinforcement, they can also greatly improve the mechanical properties of the composite material.

[0003] The preparation methods of silicon nitride nanowires include carbon thermal reduction, precursor pyrolysis, thermal evaporation, solvent thermal, direct nitridation of silicon powder and combustion synthesis. However, these methods generally have problems such as complex preparation process, difficult to accurately control the reaction, low product purity and uneven size distribution, which seriously restrict the practical application and promotion of silicon nitride nanowires. In the precursor pyrolysis method, polysilazane (PSZ) is a common precursor material for the preparation of silicon nitride nanowires. PSZ can grow nanowires under high temperature conditions, so a method for preparing silicon nitride nanowires by pyrolysis of PSZ has been developed. PSZ has a variety of structures, and PSZ of different structures can produce SiC or silicon nitride nanowires by high temperature cracking under different atmosphere conditions. Usually, in the process of preparing nanowires by precursor pyrolysis, transition metals (such as Fe, Ni, Co, etc.) are used as catalysts to accelerate the reaction process. However, this also leads to the fact that the obtained silicon nitride nanowires often contain metal impurities, further reducing the purity of the product. Therefore, how to develop silicon nitride nanowires with higher purity, simpler preparation methods and more uniform product size has become a technical problem that needs to be urgently solved in this field. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing silicon nitride nanowires. Acrylate-modified polysilazane is used as a raw material, and the prepared silicon nitride nanowires are high in purity and uniform in morphology by combining precursor pyrolysis with carbon thermal reduction. At the same time, no catalyst and toxic or harmful nitrogen source are required in the preparation process. The operation is simple, green and environmentally friendly, and the cost is low, which is suitable for large-scale industrial production.

[0005] Another object of the present invention is to provide a silicon nitride nanowire.

[0006] The technical solution adopted by the present invention is as follows: The method for preparing silicon nitride nanowires comprises the following steps: (1) Vinyl polysilazane and 2-isocyanatoethyl acrylate were mixed and stirred under vacuum conditions to obtain A-PSZ; acrylate groups were introduced by chemically modifying polysilazane. Acrylate groups contain C and O elements, which can not only catalyze the growth of silicon nitride nanowires, but also effectively reduce the curing temperature and increase the degree of crosslinking, laying the foundation for the subsequent growth of silicon nitride nanowires; (2) placing the A-PSZ in a vacuum drying oven for thermal curing to obtain cured A-PSZ; (3) Place the solidified A-PSZ in an alumina crucible, then place the crucible in a tube furnace, evacuate the furnace to a pressure of -0.1 MPa, and introduce N 2 Conducting a pyrolysis reaction at a temperature of 1500-1600°C; (4) The sample after the pyrolysis reaction in step (3) is taken out from the tube furnace, and the wool-like product generated on the surface of the sample is scraped off and collected with a knife. The product is then sequentially treated with acid and alkali to remove impurities, and finally silicon nitride nanowires are obtained.

[0007] In the step (1), the molar ratio of vinyl polysilazane to 2-isocyanatoethyl acrylate is 1:(0.45-2.28).

[0008] In the step (1), the stirring reaction is carried out at a speed of 1500-2000 rpm and for a time of 20-40 min.

[0009] In the step (2), the mass of A-PSZ is 5-20 g.

[0010] In the step (2), the thermal curing temperature is 120-200°C and the time is 2-4 hours.

[0011] In the step (3), N 2 The pressure is 0.1~0.4MPa, N 2 The flow rate is 200~500mL / min.

[0012] In the step (3), the conditions for the pyrolysis reaction are: heating to 1500-1600°C at a rate of 3-6°C / min and keeping the temperature for 1.5-3.5h.

[0013] In the step (4), a hydrochloric acid solution with a concentration of 1 mol / L is used for acid washing, and a sodium hydroxide solution with a concentration of 12 mol / L is used for alkaline washing.

[0014] In the step (4), the pickling temperature is 70-90°C and the time is 1-3 hours.

[0015] In the step (4), the alkali washing temperature is 140-160°C and the time is 1-3 hours.

[0016] The silicon nitride nanowires are prepared by using the above-mentioned method for preparing silicon nitride nanowires.

[0017] In view of the shortcomings of the existing silicon nitride nanowire preparation process, the present invention proposes a preparation method based on acrylate-modified polysilazane by combining the precursor pyrolysis method with the carbon thermal reduction principle. The principle is: by chemically modifying the vinyl polysilazane to introduce the acrylate group, the C and O element content in the system is significantly increased. The high reactivity and controllable polymerization ability of the acrylate group not only improve the processability and ceramic yield of the polysilazane, but also achieve the controllable growth of silicon nitride nanowires through the following synergistic effects: First, vinyl polysilazane reacts with 2-isocyanatoethyl acrylate to generate A-PSZ, and the C and O elements introduced play a key role in the subsequent pyrolysis process. 2 When pyrolysis is carried out under the atmosphere, Si and SiO are generated in the system. 2 、SiC、Si 3 N 4 And amorphous carbon composite ceramics. The C element promotes the transformation of solid silicon source through catalysis, and the following reactions mainly occur: SiO 2 (s)+C(s)→SiO(g)+CO(g) (Reaction 1); SiO 2 (s)+Si(s)→2SiO(g) (Reaction 2); The generated gaseous SiO and N 2 A carbon thermal reduction reaction occurs, and the reaction process is: 3SiO(g)+3C(s)+2N 2 (g)→Si 3 N 4 (s) + 3CO(g) (reaction 3); 6SiO(g)+4N 2 (g)→2Si 3 N 4 (s)+3O 2 (g) (Reaction 4); Finally, silicon nitride nanowires were grown via a vapor-solid (VS) mechanism.

[0018] In this process, the key role of the acrylate group is reflected in: 1) promoting the conversion of solid silicon source to gaseous SiO by increasing the carbon content; 2) optimizing the supersaturation of the system to provide suitable conditions for the VS growth mechanism; 3) improving the cross-linking degree of the precursor to ensure the structural integrity of the ceramic product. Finally, after acid washing and alkali washing to remove impurities, high-purity silicon nitride nanowires can be obtained.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention combines precursor pyrolysis with carbothermal reduction, uses acrylate-modified polysilazane as raw material, and controls the pyrolysis temperature, N 2 The process conditions such as pressure, flow rate and reaction time can achieve precise control of the diameter of silicon nitride nanowires (100~500nm). This method does not require the use of catalysts or toxic nitrogen sources, the process is pollution-free, and the silicon nitride conversion efficiency is high, the product grows uniformly, the operation is simple, the cost is low, and it is suitable for large-scale production; (2) The present invention is based on the curing-pyrolysis mechanism of the A-PSZ precursor. The contact area between the reaction intermediate and nitrogen is significantly increased, which promotes the preferential generation of silicon nitride nanowires on the sample surface, greatly reducing the difficulty of subsequent separation and purification. After acid washing and alkali washing, the purity of the obtained nanowires can reach more than 95%, with uniform morphology and aspect ratio > 10000, which is suitable for optoelectronics, ceramic toughening and other fields; (3) The present invention modifies polysilazane with organic functional groups through acrylate groups, which not only optimizes the crosslinking degree and ceramicization efficiency of the precursor, but also provides catalysis for the nucleation and VS mechanism growth of silicon nitride nanowires by precisely controlling the content of C and O elements, thus breaking through the limitations of traditional powder mixing methods and achieving controllable synthesis of nanowire structure and performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a scanning electron microscope image of the silicon nitride nanowires synthesized in Example 1 (×1100); Figure 2 is a scanning electron microscope image of the silicon nitride nanowires synthesized in Example 1 (×2200); Figure 3 is a scanning electron microscope image of the silicon nitride nanowires synthesized in Example 1 (×26000); Figure 4 is a scanning electron microscope image of the silicon nitride nanowires synthesized in Example 1 (×28200); Figure 5 is the XRD pattern of the silicon nitride nanowires synthesized in Example 1; Figure 6 is a diameter distribution histogram of the silicon nitride nanowires synthesized in Example 1; Figure 7is an EDS image of the silicon nitride nanowires synthesized in Example 1; Figure 8 TEM image of silicon nitride nanowires synthesized in Example 1 (×22700); Fig. 9 TEM image of silicon nitride nanowires synthesized in Example 1 (×100,000); Fig.10 TEM image of silicon nitride nanowires synthesized in Example 1 (×145000); Fig.11 TEM image of silicon nitride nanowires synthesized in Example 1 (×4250000); Fig.12 is a scanning electron microscope image (×274 times) of the silicon nitride nanowires synthesized in Comparative Example 1; Fig.13 This is a scanning electron microscope image (×2250 times) of the silicon nitride nanowires synthesized in Comparative Example 1; Fig.14 is the XRD pattern of the silicon nitride nanowires synthesized in Comparative Example 1; Fig.15 This is a diameter distribution histogram of the silicon nitride nanowires synthesized in Comparative Example 1. DETAILED DESCRIPTION

[0021] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.

[0022] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.

[0023] Some of the raw materials used in the examples and comparative examples are described as follows: Vinyl polysilazane DURAZANE 1800: purchased from Guangzhou Honghai Chemical Technology Co., Ltd.; 2-Isocyanoethyl acrylate: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0024] Example 1 The method for preparing silicon nitride nanowires comprises the following steps: (1) Vinyl polysilazane DURAZANE 1800 and 2-isocyanatoethyl acrylate were mixed in a molar ratio of 1:0.9, and stirred for reaction at 1800 rpm under vacuum for 30 min to obtain A-PSZ; (2) 10 g of A-PSZ was placed in a silicone mold, which was then placed in a vacuum drying oven, evacuated to a pressure of -0.1 MPa, and thermally cured at 140 °C for 3 h to obtain cured A-PSZ; (3) The solidified A-PSZ was removed from the silicone mold and placed in an alumina crucible. The crucible was then placed in a tube furnace and evacuated to a pressure of -0.1 MPa. N 2 Perform pyrolysis reaction and set N 2 The pressure is 0.2MPa, N 2 The flow rate was 400 mL / min; the conditions for the pyrolysis reaction were: heating to 1500°C at a rate of 5°C / min and keeping warm for 2 h; (4) After the reaction was completed, the temperature was lowered to 100°C at a rate of 3°C / min, and then naturally cooled to room temperature. The sample after the pyrolysis reaction was taken out of the tube furnace, and the wool-like product generated on the surface of the sample was scraped off and collected with a knife. Then, the product was first acid-washed with a 1 mol / L hydrochloric acid solution at 80°C for 2 h, and then alkaline-washed with a 12 mol / L sodium hydroxide solution at 150°C for 2 h. Finally, silicon nitride nanowires were obtained, and their diameter was measured to be 260±76nm and their aspect ratio was 11056. X-ray diffraction analysis was used to characterize the crystal phase of the target product. The peak data of the obtained XRD spectrum were integrated, and the ratio of the β-silicon nitride peak area to the total integrated area was calculated, and its purity was 98.7%.

[0025] The silicon nitride nanowires were characterized using scanning electron microscopy, X-ray diffractometer, energy dispersive spectrometer and transmission electron microscopy. Figures 1 to 11 shown.

[0026] Figures 1 to 4 This is a scanning electron microscope image of the silicon nitride nanowires synthesized in Example 1. It can be seen from the figure that the silicon nitride nanowires show an epitaxial oriented growth mode on the surface of the bulk substrate. The nanowires show a uniform linear growth morphology and have no obvious structural defects.

[0027] Figure 5 The XRD spectrum of the silicon nitride nanowires synthesized in Example 1 shows that the prepared silicon nitride nanowires are mainly β-silicon nitride (PDF#33-1160), and some α-silicon nitride also exists. In addition, the C and O elements remaining in the precursor react at high temperature to generate β-SiC and SiO 2 These secondary phases mainly appear in the sample matrix and have little effect on the purity of silicon nitride nanowires.

[0028] By measuring the diameter of the silicon nitride nanowires in the scanning electron microscope image, a diameter distribution histogram of the silicon nitride nanowires is obtained. Figure 6 As shown in the figure, it can be seen that the average diameter of silicon nitride nanowires is 260±76nm (CV=29.2%).

[0029] Figure 7 This is the EDS image of the silicon nitride nanowires synthesized in Example 1. It can be seen from the figure that the prepared silicon nitride nanowires are mainly composed of Si (32.63at%) and N (47.24at%) elements (the atomic ratio is about 3:4), and a small amount of O (7.69at%) and C (12.44at%) are also detected.

[0030] Figures 8 to 11 This is a TEM image of the silicon nitride nanowires synthesized in Example 1. It can be seen from the figure that the prepared silicon nitride nanowires have a typical cylindrical cross-section, the diameter is highly uniform along the axial direction, and no second phase particle attachment phenomenon is observed. It is also observed that: 1) no metal catalyst droplets are detected at the tip of the nanowire, and this morphological feature excludes the possibility of a gas-liquid-solid (VLS) growth mechanism; 2) the nanowires show an axial growth mode along the

[102] crystal direction, which is consistent with the typical characteristics of the gas-solid (VS) growth mechanism; 3) Fig.11 A β-Si with a (210) interplanar spacing of 0.258 nm can be observed. 3 N 4 and β-Si with a lattice spacing of 0.269nm (102) 3 N 4 , which is consistent with the data measured by XRD, confirming that the obtained nanowires are mainly β-Si 3 N 4 .

[0031] Example 2 The method for preparing silicon nitride nanowires comprises the following steps: (1) Vinyl polysilazane DURAZANE 1800 and 2-isocyanatoethyl acrylate were mixed in a molar ratio of 1:0.45, and stirred for reaction at 1500 rpm under vacuum for 40 min to obtain A-PSZ; (2) 5 g of A-PSZ was placed in a silicone mold, which was then placed in a vacuum drying oven, evacuated to a pressure of -0.1 MPa, and thermally cured at 120 °C for 4 h to obtain cured A-PSZ; (3) The solidified A-PSZ was removed from the silicone mold and placed in an alumina crucible. The crucible was then placed in a tube furnace and evacuated to a pressure of -0.1 MPa. N 2 Perform pyrolysis reaction and set N 2 The pressure is 0.1MPa, N 2The flow rate was 500 mL / min; the conditions for the pyrolysis reaction were: heating to 1550°C at a rate of 3°C / min and keeping warm for 1.5 h; (4) After the reaction was completed, the temperature was lowered to 100°C at a rate of 3°C / min and then naturally cooled to room temperature. The sample after the pyrolysis reaction was taken out of the tube furnace and the wool-like product generated on the surface of the sample was scraped off and collected with a knife. Then, the product was first acid-washed with a 1 mol / L hydrochloric acid solution at 70°C for 3 h, and then alkaline-washed with a 12 mol / L sodium hydroxide solution at 140°C for 3 h. Finally, silicon nitride nanowires were obtained with a purity of 98.1%, a diameter of 250±63 nm, and an aspect ratio of 13025.

[0032] Example 3 The method for preparing silicon nitride nanowires comprises the following steps: (1) vinyl polysilazane DURAZANE 1800 and 2-isocyanatoethyl acrylate were mixed in a molar ratio of 1:2.28, and stirred for reaction at 2000 rpm under vacuum for 20 min to obtain A-PSZ; (2) 20 g of A-PSZ was placed in a silicone mold, which was then placed in a vacuum drying oven, evacuated to a pressure of -0.1 MPa, and thermally cured at 200 °C for 2 h to obtain cured A-PSZ; (3) The solidified A-PSZ was removed from the silicone mold and placed in an alumina crucible. The crucible was then placed in a tube furnace and evacuated to a pressure of -0.1 MPa. N 2 Perform pyrolysis reaction and set N 2 The pressure is 0.4MPa, N 2 The flow rate was 200 mL / min; the conditions for the pyrolysis reaction were: heating to 1600°C at a rate of 3°C / min and keeping warm for 1.5 h; (4) After the reaction was completed, the temperature was lowered to 100°C at a rate of 3°C / min and then naturally cooled to room temperature. The sample after the pyrolysis reaction was taken out of the tube furnace and the wool-like product generated on the surface of the sample was scraped off and collected with a knife. Then, the product was first acid-washed with a 1 mol / L hydrochloric acid solution at 90°C for 1 h, and then alkaline-washed with a 12 mol / L sodium hydroxide solution at 160°C for 1 h. Finally, silicon nitride nanowires were obtained with a purity of 99.3%, a diameter of 235±42 nm, and an aspect ratio of 15489.

[0033] Comparative Example 1 The difference from Example 1 is that the conditions for the pyrolysis reaction in step (3) are: heating to 1450° C. at a rate of 5° C. / min and keeping warm for 2 h. The rest is the same as Example 1.

[0034] The silicon nitride nanowires were characterized using scanning electron microscopy and X-ray diffractometer. Figures 12 to 15 shown.

[0035] Figures 12-13 The scanning electron microscope image of the silicon nitride nanowires synthesized in Comparative Example 1 is shown. The diameter of the silicon nitride nanowires in the image is measured and a diameter distribution histogram of the silicon nitride nanowires is obtained. Fig.15 As shown in the figure, it can be seen that the average diameter of silicon nitride nanowires at 1450°C is 230±99nm (CV=43%), while the average diameter of the sample treated at 1500°C increases to 260±76nm (CV=29.2%). This shows that increasing the pyrolysis temperature not only makes the silicon nitride nanowires moderately coarsened, but also narrows the diameter distribution range by about 33%, reflecting the homogenization regulation effect of high temperature conditions on the growth process.

[0036] Fig.14 The XRD spectrum of the silicon nitride nanowires synthesized in Comparative Example 1 shows that when the pyrolysis temperature is 1450°C, the product is mainly amorphous, showing only a broadened diffraction envelope. As the pyrolysis temperature rises to 1500°C, the crystallinity of the material is significantly improved, and multiple characteristic diffraction peaks can be observed. It can be seen that after high-temperature pyrolysis of A-PSZ, β-Si 3 N 4 phase, but when the treatment temperature reaches 1500℃, α-Si 3 N 4 Most of it has been transformed into β-Si 3 N 4 This phase transition process may be due to the higher thermodynamic stability of the β phase under high temperature conditions. In addition, the residual C and O elements in the precursor reacted at high temperature to generate β-SiC and SiO 2 This discovery confirms the multiphase co-evolution characteristics of the A-PSZ system under high temperature environment, and provides an important theoretical basis for the subsequent material performance regulation.

[0037] From the above, it can be concluded that the 1500℃ pyrolysis conditions optimize the gas-solid reaction balance, making silicon nitride nanowires show significant advantages in growth density and size uniformity (CV value reduced by 32%), providing an important process reference for the controllable synthesis of high-performance silicon nitride nanomaterials.

Claims

1. A method for preparing silicon nitride nanowires, characterized in that: The following steps are involved: (1) Vinyl polysilazane and 2-isocyanatoethyl acrylate are mixed and stirred under vacuum conditions to obtain A-PSZ; (2) placing the A-PSZ in a vacuum drying oven for thermal curing to obtain cured A-PSZ; (3) placing the solidified A-PSZ into a tubular furnace and introducing N2 for pyrolysis reaction at a temperature of 1500-1600°C; (4) The sample after the pyrolysis reaction in step (3) is taken out from the tube furnace, the product generated on the surface of the sample is collected, and acid washing and alkali washing are performed in sequence to finally obtain silicon nitride nanowires.

2. The method for preparing silicon nitride nanowires according to claim 1, characterized in that: In the step (1), the molar ratio of vinyl polysilazane to 2-isocyanatoethyl acrylate is 1:(0.45-2.28).

3. The method for preparing silicon nitride nanowires according to claim 1, characterized in that: In the step (1), the stirring reaction is carried out at a speed of 1500-2000 rpm and for a time of 20-40 min.

4. The method for preparing silicon nitride nanowires according to claim 1, characterized in that: In the step (2), the thermal curing temperature is 120-200°C and the time is 2-4 hours.

5. The method for preparing silicon nitride nanowires according to claim 1, characterized in that: In the step (3), the pressure of N2 is 0.1-0.4 MPa, and the flow rate of N2 is 200-500 mL / min.

6. The method for preparing silicon nitride nanowires according to claim 1, characterized in that: In the step (3), the conditions for the pyrolysis reaction are: heating to 1500-1600°C at a rate of 3-6°C / min and keeping the temperature for 1.5-3.5h.

7. The method for preparing silicon nitride nanowires according to claim 1, characterized in that: In the step (4), a hydrochloric acid solution with a concentration of 1 mol / L is used for acid washing, and a sodium hydroxide solution with a concentration of 12 mol / L is used for alkaline washing.

8. The method for preparing silicon nitride nanowires according to claim 1, characterized in that: In the step (4), the pickling temperature is 70-90°C and the time is 1-3 hours.

9. The method for preparing silicon nitride nanowires according to claim 1, characterized in that: In the step (4), the alkali washing temperature is 140-160°C and the time is 1-3 hours.

10. A silicon nitride nanowire, characterized in that: The silicon nitride nanowires are prepared by the method for preparing the silicon nitride nanowires according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silicon nitride ceramic and preparation method thereof

    CN108675798A

  • Polysilazane modified epoxy single-component anticorrosive coating slurry, coating and preparation method

    CN111961412A

  • Preparation method and application of photocurable silicon nitride ceramic slurry

    CN118084512A

  • Process for synthesizing based si-based one-dimensional nano material

    CN1724466A

  • beta-Si3N4 NANOWIRE, METHOD FOR PRODUCTION OF THE SAME, AND RESIN COMPOSITION USING THE SAME

    JP2011079729A

Cited By

  • Method for enhancing oral all-ceramic material through SiC nanowire in-situ decarburization and application of oral all-ceramic material

    CN122277272A